RECONSTRUCTION OF NUSYÚZ CONCEPT IN COMPILATION OF ISLAMIC LAW IN INDONESIA (Gender Equality Perspective Analysis) - Fitri, Al; Alamsyah, A.; Sadari, S.; Susanto, Is (SMART: Journal of Sharia, Traditon, and Modernity, 2021)
Nusyúz is a classical conception codified as a standard law written in Qs. an-Nisáa’ verses 34 and 128. The conventional fiqh perspective of nusyúz connotes the wife’s disobedience to her husband, because it is influenced by the patriarchy of pre-Islamic Arab culture. Presidential Instruction Number 1 of 1991 concerning the Compilation of Islamic Law in Indonesia mentions nusyúz in Articles 80, 84 and 125, only regulates the wife’s nusyúz and its legal sanctions, while the husband’s nusyúz is not mentioned. There is ambivalence, ambiguity and legal injustice for the wife. The focus of this research is the concept of nusyúz in KHI from a gender perspective and its correlation with the development of family law in Indonesia. This type of research is library research with a gender equality analysis approach. The results of this study indicate that it is necessary to rearrange the concept of nusyúz in the KHI, including the modern era understanding of nusyúz and adding the husband's concept of nusyúz and its legal sanctions in KHI.Keywords:     Nusyúz Modern Era, Gender Perspective, Justice.